1967
DOI: 10.1029/jz072i020p04999
|View full text |Cite
|
Sign up to set email alerts
|

Hugoniot equation of state of twelve rocks

Abstract: Shock‐wave data have been obtained for the following rocks: one albitite, one anorthosite, two bronzitites, two diabases, two dunites, two eclogites, one granite, and one Jadeite. The experimental pressure range is from slightly over 0.1 to about 1.0 Mb. There is evidence that all rocks investigated exhibit a phase change. It is estimated that the transformations occur at about 0.1 Mb for the low‐density rocks and between 0.3 and 0.6 Mb for the high‐density rocks. A single‐shock Hugoniot consistent with the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2

Year Published

1970
1970
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(91 citation statements)
references
References 19 publications
4
85
2
Order By: Relevance
“…To avoid additional complexity, we use a simple linear equation of state derived from the Rankine-Hugoniot equations for jump conditions connecting physical parameters at a discontinuity like a shock. In most solids, it has been found that Erosion at geometric strain 0.9 none the velocity of the impact, U p , and the velocity of the shock front U s , follow a linear relationship: Marsh & Fritz 1967). This is used together with a Mie-Grneisen form of the equation of state (Mie 1903;Grüneisen 1912) based on the principal Hugoniot that connects every possible state described by density, shock velocity, and specific internal energy , U s , and e reachable after a shock from the initial set of 0 , U p , and e 0 :…”
Section: Sph Simulations and Materials Parametersmentioning
confidence: 99%
“…To avoid additional complexity, we use a simple linear equation of state derived from the Rankine-Hugoniot equations for jump conditions connecting physical parameters at a discontinuity like a shock. In most solids, it has been found that Erosion at geometric strain 0.9 none the velocity of the impact, U p , and the velocity of the shock front U s , follow a linear relationship: Marsh & Fritz 1967). This is used together with a Mie-Grneisen form of the equation of state (Mie 1903;Grüneisen 1912) based on the principal Hugoniot that connects every possible state described by density, shock velocity, and specific internal energy , U s , and e reachable after a shock from the initial set of 0 , U p , and e 0 :…”
Section: Sph Simulations and Materials Parametersmentioning
confidence: 99%
“…The elastic moduli and the pressure derivatives can be estimated by fitting the Birch-Murnaghan (B-M) equation to the isothermal compression curve. Figure 1 show the Hugoniot data of quartz [9][10][11], the derived isothermal compression curve and the B-M fitting curves, Fig, 1. Hugoniot analytical results, together with the static X-ray date [1] and the B-M equation curves using ultrasonic and Brillouin scattering data of stishovite [5 ,13,14].…”
Section: Thermal Analysis Proceduresmentioning
confidence: 99%
“…But, the analysis is confusing for SiO2, because the Gruneisen parameters of quartz and stishovite are very different, and the internal energy changes due to phase transition. In this study, we analyzed the Hugoniot data of quartz [9][10][11] to discuss the EOS of the stishovite and thefurther phase transitions, considering the changes in Gruneisen parameter and internal energy due to the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…For the pure alumina ceramics, the limit ing value of a is between 1.01 and 1.02, corresponding to values of Ac* between 20 and 40 kbar. The exact values are given in Table 6, where the value of the stress offset corresponding to the HEL is also 36 …”
Section: [-I-i-i-|-i-i-i-i-i-mentioning
confidence: 99%